Pelatihan Dapur Sehat Atasi Stunting di Lokasi Fokus (Lokus) Penanganan Stunting Kabupaten Boyolali - Monikasari Monikasari; Sarah Melati Davidson; Gelora Mangalik; Kristiani Desimina Tauho; Ayu Afriani Panyuwa; Dary Dary; Brigitte Sarah Renyoet; Rifatolistia Tampubolon; Kristiawan Prasetyo Agung Nugroho (Jurnal Abdimas Kesehatan (JAK), 2023)
Stunting is a condition in which a child's height is shorter than that of other children of the same age. Children experiencing stunting can be caused by several factors such as poor nutrition experienced by pregnant women and toddlers, lack of knowledge of mothers about health and nutrition that occurs before pregnancy and after childbirth, limited health services, lack of access to nutritious food and lack of access clean water and sanitation. In addition, the practice of giving food to toddlers is something that must be considered, is one way to meet the nutritional needs of toddlers. A good feeding pattern for toddlers will have an impact not only on physical growth but also on their cognitive-mental development. The mother as caregiver has all the decisions regarding healthy feeding practices, including breastfeeding. Giving food to toddlers is closely related to the role of the mother. Mother's education is an important factor that indirectly affects nutritional status, because mother's education will affect parenting patterns for children. The form of community service activities is in the form of delivering material on balanced nutrition, stunting and cooking training. A pre test was carried out before the extension activities with the results of the mother's knowledge level regarding stunting and healthy food, food safety with results of 77.12-80.66, for the post test results given after the delivery of the material and after cooking training, there was an increase in the mother's knowledge about stunting and good food processing and correct at 83.32-86.85. The conclusion is that there is an increase in mother's knowledge regarding stunting and proper and proper food processing which has a direct effect on mother's awareness regarding family nutrition and family health.